WOUND HEALING ACTIVITY OF UNGUENTUM DOSAGE FORM OF ETHANOLIC EXTRACTS OF Areca catechu L. NUT IN Mus musculus albinus - Azizah Vonna; Rizky Nurismi; Misrahanum . (Universitas Syiah Kuala, 2015)
The activity test of ethanol extract of betel nut ointment (Areca catechu L.) in wound healing on mice (Mus musculus albinus) has been carried out to determine the ability of the ethanol extract of betel nut ointment in wound healing and determine the concentration which was accelerate the wound healing on mice between 2 concentrations. This experimental research method used completely randomized design (CRD) using 20 mices divided into 4 treatment groups ; ointment base, povidone iodine ointment, ethanol extract of betel nut ointment (SEEBP) 2% and SEEBP 4%. Each treatment groups was tested in the incision which was made along the 15 mm parallel to the spine (Os. Vetebre) with the depth until subcutaneous skin layers. The ointment was applied twice a day for about 21 days and observed changes every day for during the period of observation. The results showed that the average length of time of the scab formation, the scab exfoliation, and the wound healing successively are for the ointment base was 6.6; 10.2 and 18.2 days, povidone iodine ointment was 7; 11.2 and 14.8 days, SEEBP 2% was 5.75; 7.75 and 13.25 days, SEEBP 4% was 4.2; 8.8 and 12.8 days. ANOVA and LSD results of scab formation time showed a significant difference between SEEBP 4% with base ointment and povidone iodine ointment (p 0.05). Results of the exfoliation scab showed a significance difference between SEEBP 2% with base ointment and povidone iodine ointment (p 0.05). The duration of wound healing showed that there was significance difference between SEEBP 2%, SEBP 4% and povidone iodine ointment with ointment base (p0.05).Thus, betel nut ointment as an effect on healing process. The concentration which can accelerate wound healing in mice is SEEBP 4%.